Tren Peran Guru Bimbingan Dan Konseling Dalam Mencegah Perundungan Di Sekolah Periode 2019-2023 - Lestari, Dyah Muji; Pawitraningtyas, Ken Ayya Syarifah; Rahmatika, Putri Fitri; Nabilah, Jaisy Hanun; Muslikah, Muslikah; Mahfud, Ashari (CV. Ulil Albab Corp, 2024)
This research examines the trends in strategies implemented by guidance and counseling (BK) teachers in preventing bullying during the 2019-2023 period. This research uses a literature study method by analyzing various sources of literature which aims to identify the development of approaches implemented by guidance and counseling teachers to overcome bullying. The results of the analysis show that there is consistency in the utilization of basic services, responsive interventions, and collaboration with various parties carried out by guidance and counseling teachers. There is a significant improvement with the presence of the Merdeka Curriculum which provides more opportunities for students to explore anti-bullying values. This study also identified an increase in the role of technology in efforts to prevent bullying, the need and importance of the role of parents, and comprehensive and sustainable school policies. Data from the Central Bureau of Statistics shows a change in bullying cases occurring in Central Java with the age range of 0-18 years, with a significant increase occurring in 2023 to 1,327 cases. This study aims to provide a foundation for the development of a more effective bullying prevention program for the future, focusing on establishing a safe and supportive school environment for all students.